Chapter 13 Enabling Nanomilling through Control of Particulate Interfaces - Peukert, Wolfgang; Sommer, Marc (Elsevier B.V., 2007)
The postulated grinding limit at around half a micron that has existed for decades does not exist. Particle sizes down to 10 nm can be obtained. Nanomilling in aqueous and non-aqueous media becomes possible when the particulate interfaces are carefully controlled to prevent agglomeration of the broken fragments. Particle stability ensures also low suspension rheology. Any influence of the type of mill is not pronounced, if it exists at all. Important features are small milling beads, a high energy density in the mill, i.e. stirrer speeds in the range of 6-12 m/s and inhibition of agglomeration. Stabilization must be faster than the breakage kinetics. The latter can be estimated from population balance models. Ionic stabilization is preferable wherever it works because this mechanism is rather simple and can be detected on-line during milling by means of electro-acoustic spectroscopy. Even though stabilization can be achieved by the steric mechanism more research is necessary to understand details of the stabilization process. Nanomilling is a neat example which shows that real breakthroughs become possible even in very old and traditional technologies by fundamental studies of the underlying mechanisms. Nanomilling became, thus, an option for those who look for simple and versatile processes to nanoparticles. © 2007.
Keywords: nano; particle; milling; interface; interaction; energy